Quality improvement strategies to optimise transition of patients with heart failure to independent living: protocol for a scoping review. Issue 11 (27th November 2014) - Kastner, Monika; Lillie, Erin; Ashoor, Huda; Perrier, Laure; Cardoso, Roberta; Straus, Sharon; Lee, Douglas S
Abstract : Introduction: Heart failure (HF) is a leading reason for hospitalisation and readmissions to hospital, particularly among individuals older than 65 years of age. The prognosis of patients with HF is grim, with high rates of mortality risk and hospital readmissions. The transition period early after hospital discharge represents a window of opportunity to positively influence patient outcomes using quality improvement (QI) strategies. However, little is known about which QI interventions exist for early events of HF after discharge, so the main objective of our study is to conduct a scoping review of the literature to determine which QI strategies are effective for reducing hospital readmissions and mortality for patients with HF who transition from the hospital back into independent living. We will also investigate which elements contribute to effective QI strategies. Methods and analysis: We will search the literature in MEDLINE, EMBASE, CINAHL and the Cochrane library for randomised controlled trials and systematic reviews evaluating QI interventions aimed at improving outcomes for patients with HF transitioning from the hospital back into the community. Two reviewers will independently apply our eligibility criteria at level 1 (abstract/title) and level 2 (full-text) screening; disagreements will be resolved through consensus. We will extract data in duplicate on study characteristics, population, setting, QI intervention and outcomes. We will synthesise results descriptively and explore QI elements to determine which aspect contributes to its impact. We will also consider synthesis of our data according to several conceptual frameworks such as Wagner's Chronic Care Model. Discussion and dissemination: The findings of this scoping review will be used to determine which elements should comprise a QI intervention aimed at facilitating the transition of newly admitted patients with HF back into the community. We will disseminate our findings through publications, presentations as well as through a stakeholder meeting to generate key messages most relevant to each.